(untitled) (Nepalese Veterinary Journal, 2017)
Wild birds are the carrier of Avian influenza virus as reservoir. They spread virus through faecal drops. Considering this fact, a study was carried out to detect the avian influenza virus in fresh fecal swabs in Chitwan National Park, Sauraha. A total of 40 samples were collected from Baghmara Buffer zone community forest,30 samples from Rapti river bank and 10 samples from National trust for nature conservation areas. The faecal samples were collected during the summer season (March). The test was carried out by using a rapid test kit (synbiotic kit) USA. On rapid test, all the 80 samples were negative. All 80 samples were further inoculated in nine days embryonated eggs for haemagglutination tests for the confirmative diagnosis that showed negative result. Preliminary diagnosis revealed that wild birds were free from Avian Influenza in Chitwan National Park region.